Multi-well micropatterning by ablation - BHATIA SANGEETA N; EDDINGTON DAVID T (2008)
The present invention is drawn to the generation of micropatterns of biomolecules and cells on standard laboratory materials through selective ablation of a physisorbed biomolecule with oxygen plasma. In certain embodiments, oxygen plasma is able to ablate selectively physisorbed layers of biomolecules (e.g., type-I collagen, fibronectin, laminin, and Matrigel) along complex non-linear paths which are difficult or impossible to pattern using alternative methods. In addition, certain embodiments of the present invention relate to the micropatterning of multiple cell types on curved surfaces, multiwell plates, and flat bottom flasks. The invention also features kits for use with the subject methods.